A review on grammatical gender acquisition in monolingual Spanish-speaking children - Ogneva, Anastasiia (Onomázein, 2023)
Acquisition of grammatical gender has been well addressed in psycholinguistic research with Spanish monolingual typically developing (TD) children but less with children diagnosed with Developmental Language Disorder (DLD). The present article reviews linguistic and psycholinguistic studies on grammatical gender acquisition from different methodologies across monolingual Spanish-speaking children with typical language development and children diagnosed with DLD. Specifically, we explore how typically developing and DLD children assign grammatical gender and establish gender agreement. We discuss the implication of the findings for the design of the future research on gender acquisition.